Do more faster techstars lessons to accelerate your startup - Cohen, David G.; Feld, Brad (Hoboken, N.J. Wiley, 2011)
Practical advice from some of today's top early stage investors and entrepreneurs TechStars is a mentorship-driven startup accelerator with operations in three U.S. cities. Once a year in each city, it funds about ten Internet startups with a small amount of capital and surrounds them with around fifty top Internet entrepreneurs and investors.
Includes index.
Keywords: New business enterprises -- Management; Entrepreneurship; Business